Las condiciones individuales como elemento de la culpabilidad: Un análisis crítico de los supuestos de inimputabilidad en el Código Penal peruano - Anaya Laime, Noelia Jackelin (2025)
This article critically addresses the assumptions for non-imputability established in the Peruvian Penal Code and demonstrates that the treatment of culpability from a strictly legal perspective is currently insufficient. For that purpose, it first briefly reviews culpability as a category that encompasses non-imputability. It then analyzes each ground for non-imputability: minority (with the exception established in Law Nº 32330), «mental abnormality», and serious alteration of consciousness. For each, a delimitation is proposed based on doctrine, considering the contributions of neuroscience and psychiatry. It also verifies that some legislative initiatives, as well as the ravages of the inquisitorial system, have generated the erroneous impression that non-imputability is a space of impunity. Therefore, there is a need to firmly respect the unculpability of minors, reconsider the scope of «mental abnormality», and more rigorously address the serious disturbance of consciousness.